Institutional and Policy Analysis of River Basin Management : The Gudalquivir River Basin, Spain - Blomquist, William (World Bank, Washington, DC, 2012)
The authors describe and analyze river basin management in the Guadalquivir River Basin in Spain. The Guadalquivir river flows westerly across southern Spain, with nearly all of its 57,017 k